2016
DOI: 10.1051/matecconf/20166204003
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Electrochemical Characterization of Palm Kernel Shell Biochar (PKSB) as Supercapacitor

Abstract: Abstract.A potential low cost and environmentally friendly supercapacitor has been prepared from Palm Kernel Shell Biochar (PKSB). In this study, physical and electrochemical properties of raw, activated and chemical treated (potassium hydroxide (KOH)) as supercapacitors such as high carbon content, high charge storage capacity and stable were evaluated. For physical analyses, the scanning electron microscopy (SEM) was used to study the surface morphology and surface area and porosity were measured using Bruna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Based on the D/G peak area ratio, the D-band peaks are significantly stronger than the G-band which indicates that most of the graphitic carbon is disordered [28]. Measuring the I D /I G may reveal the changes in biochar properties especially about the sp 2 bonding, typically of those concerning to the use of chemical reagents to modify the material [31].…”
Section: Raman Analysis For Pks Biocharmentioning
confidence: 99%
“…Based on the D/G peak area ratio, the D-band peaks are significantly stronger than the G-band which indicates that most of the graphitic carbon is disordered [28]. Measuring the I D /I G may reveal the changes in biochar properties especially about the sp 2 bonding, typically of those concerning to the use of chemical reagents to modify the material [31].…”
Section: Raman Analysis For Pks Biocharmentioning
confidence: 99%
“…Several studies on PKS characterization, carbonization, pyrolysis and gasification have been reported. In most of these studies; obtaining activated carbon between temperature of 500 to 900 °C was the focus of studies conducted by Ghani et al (2016); Yashim et al (2016) and Nicholas et al (2018). While others investigated the effects of carbonization at temperature of 500 to 700 or 900 °C on the char without activation (Daud et al, 2001;Yang et al, 2006;Okoroigwe and Saffron, 2012;Lee et al, 2017;Wang et al,2018).…”
Section: Introductionmentioning
confidence: 99%